2020
DOI: 10.1016/j.acap.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician Attitudes Toward and Experiences With Telehealth Use: Results From a National Survey

Abstract: BACKGROUND:The American Academy of Pediatrics 2015 policy statement on telehealth proposed that telehealth could increase access to high-quality pediatric care and that pediatricians should work to reduce barriers to telehealth for their patients. However, little is known about pediatricians' experiences with and attitudes toward telehealth.METHODS: Data from a nationally representative survey of American Academy of Pediatrics postresidency US member pediatricians in 2016, restricted to respondents providing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 6 publications
5
68
0
1
Order By: Relevance
“…According to these results, prior to the pandemic approximately 14.5% of those surveyed were utilizing telehealth. This number is very similar to estimates obtained from pediatricians where it was reported that 15% had utilized telehealth in the year prior to a survey completed in 2016, with slightly higher numbers for specialists and those practicing in a rural setting [9]. In an article by North, among family physicians and pediatricians in the United States, there was an increase from 11.8% using telehealth from 2016 with an increase to 91% of primary care physicians using telehealth 2 months into the pandemic [10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to these results, prior to the pandemic approximately 14.5% of those surveyed were utilizing telehealth. This number is very similar to estimates obtained from pediatricians where it was reported that 15% had utilized telehealth in the year prior to a survey completed in 2016, with slightly higher numbers for specialists and those practicing in a rural setting [9]. In an article by North, among family physicians and pediatricians in the United States, there was an increase from 11.8% using telehealth from 2016 with an increase to 91% of primary care physicians using telehealth 2 months into the pandemic [10].…”
Section: Discussionsupporting
confidence: 84%
“…Houtrow et al [11] reported in 2010-2011 that almost 6 million children were considered disabled, comprising nearly 8% of the population. Additionally, the incidence rate of disability has increased in the period from 2001-2002 to 2010-2011 [9]. According to the American Board of Physical Medicine and Rehabilitation, since 2003, only 308 board certifications in Pediatric Physiatry have been issued [12].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-pandemic, children with disabilities were underserved by the health care system that wasn't organized to meet their needs [15,17,55]. The pandemic brought forward the need to provide remote health care through telehealth which was rarely used prepandemic [61]. But access to telehealth is inequitable as some families don't have reliable internet service or the devices needed to conduct a telehealth visit [62].…”
Section: Optimizing Equitable Care For Children With Disabilities Durmentioning
confidence: 99%
“…13 However, a survey of paediatric caregivers showed that only 15% of paediatricians had used telehealth. 14 The American Academy of Pediatrics (AAP) National Coordinating Center for Epilepsy has worked to test and establish a multifaceted system to ensure that CYE, particularly those in medically underserved and/or rural areas, have access to the medical, social and other supports and services required to achieve optimal health outcomes and improved quality of life. The Access Improvement and Management of Epilepsy with Telehealth (AIM-ET) project was designed by the Center to help alleviate barriers to health care for CYE.…”
Section: Introductionmentioning
confidence: 99%